022 Nitrous oxide induced myelo-neuropathy. (23rd August 2021) - Swart, Grace; Blair, Christopher; Lu, Zhong X; Yogendran, Solomon; Offord, Joanna; Sutherland, Emily; Barnes, Stephanie; Palavra, Natalie; Cremer, Phillip; Bolitho, Samuel; Halmagyi, Gabor M
Abstract : Background: Nitrous oxide misuse is a recognized issue worldwide. It is cheap, legal and can be bought in bulk online. Prolonged misuse inactivates vitamin B12 causing a myelo-neuropathy. Methods: Review of 20 patients with nitrous-oxide induced myelo-neuropathy from tertiary hospitals between 2016-2020 Results: Twenty patients had an average age of 25 years. Mean canister consumption was 150 per day for 9 months. At presentation paraesthesia and gait unsteadiness were common, and six patients were bedbound. Mean serum B12 was normal: 258 pmol/L(NR=140-750) as was active B12: 94 pmol/L(N>35). In contrast mean serum homocysteine was high: 51 umol/L(NR=5-15). Spinal MRI(n=19) showed characteristic dorsal column T2 hyperintensities. Nerve conduction studies(n=5) showed a lower limb predominant axonal sensorimotor neuropathy. Patients were treated with intramuscular vitamin B12, with variable functional recovery at discharge. Three of 6 patients who were bedbound at presentation were able to walk with an aid at discharge. Of 8 patients with follow-up, most had persistent paraesthesiae and/or sensory ataxia. Admission and discharge mobility scores were not significantly correlated with serum total and active B12 levels or cumulative nitrous oxide use. However, there was an inverse trend for decreased serum active B12 level with increased cumulative nitrous oxide use (Spearman's rho -0.416, p=0.09). Conclusion: Nitrous oxide misuse can cause severe but potentially reversible subacute myelo-neuropathy. Serum and active B12 can be normal, while elevated homocysteine and dorsal column high T2 signal on MRI imaging strongly support the diagnosis. Neurological deficits can improve with abstinence and B12 replacement, even in the most severely affected patients.